Estimation of passing sight distance required for operation of truck platooning on two-lane highways in North America - Tanvir Chowdhury; Peter Y. Park; Kevin Gingerich (IATSS Research)
The most well-known benefits of heavy commercial vehicle (HCV) platooning include fuel savings and emission reductions. In addition, HCV platooning under SAE automation level 4 or 5 can mitigate the truck driver shortage in North America by eliminating the driver from one or more HCVs in a platoon. This study investigates the passing sight distance (PSD) required to overtake a truck platoon or long combination vehicle (LCV). The PSD is one of the most important highway geometric design parameters. This study modified the 2018 AASHTO's PSD model for HCV platooning and long combination vehicles (LCVs). A micro-simulation model is used to validate the outcomes of the modified AASHTO model. The estimated PSDs suggest that it may be possible to operate two-HCV platoons on two-lane highways that already allow LCV operation if appropriate passing lanes are installed. The study's approach and findings are expected to help transportation engineers and government agencies prioritize two-lane highway sections for possible HCV platooning operation.